Numerical methods for scientists and engineers - Antia, H. M. (Tata McGraw-Hill Pub. Co., 1991)
This book presents an exhaustive and in-depth exposition of the various numerical methods used in scientific and engineering computations. It emphasises the practical aspects of numerical computation and discusses various techniques in sufficient detail to enable their implementation in solving a wide range of problems.